Skating School: Scarlet Skate Magic - Chapman, Linda (Penguin Group, 2010)
Welcome to a magical world where dreams come true . . . Emily and her skating-school friends can't wait to go on an exciting two-day scavenger hunt. The girls must work in teams and they all want to win the very special scarlet skates. But will they discover that listening to each other is even greater than winning?
Keywords: Juvenile literature-Fiction